"To be healthier and more beautiful": medicines and cosmetics in press advertisements of the imperial province of Bukovina (1880-1910) = "Być zdrowszym i piękniejszym". Leki i kosmetyki w reklamach prasowych imperialnej prowincji Bukowiny (1880-1910) - Sabol, Harieta Mareci (Zielona Góra: Lubuskie Towarzystwo Naukowe)
At the turn of the 19th and 20th centuries, the trade in therapeutic goods and their internal distribution experienced rapid growth in Bukovina, the easternmost province of the Austrian Empire. This process saw the establishment of new pharmacies and depots that sold products intended to restore health and enhance beauty.
Keywords: leki; kosmetyki; rynek; apteka; reklama; medicines; cosmetics; market; pharmacies; advertisement